The Influence of Vegetative Propagation Model on the Growth of Cultivar Plant Seedlings (Citrus reticulate): Pengaruh Model Perbanyakan Vegetatif Terhadap Pertumbuhan Bibit Tanaman Cultivar Jeruk Siompu (Citrus reticulate) - Zainun Zainun; Sri Yuniati (JURNAL AGRIYAN: JURNAL AGROTEKNOLOGI UNIDAYAN, 2021)
Siompu oranges are one of the national mainstay tangerines which were initially only found on Siompu Island, South Buton Regency. One of the causes of the lack of availability of siompu citrus seeds is the relatively long time to obtain seeds that are ready for planting from the seeds. This study aims to determine the vegetative propagation model that affects the successful growth of siompu citrus plants. The research was carried out from March to May 2020, in Kaimbulawa Village, Siompu District, South Buton Regency, Southeast Sulawesi Province. The study used a completely randomized design (CRD) consisting of one factor, namely vegetative propagation with 3 treatments; P1 = cuttings, P2 = shoot, and P3 connection= grafting. If the F count is greater than the F table at the 95% level, then continue with the LSD test at the 95% level. The responses observed were time of shoot appearance (days), number of shoots, number of leaves (strands) and percentage of life (%). Based on the results of the study, shoot grafting was the best treatment which had a high average number of shoots, number of leaves and percentage of life. Keywords: Citrus Siompu (Citrus reticulate), Cuttings, Sampung shoots, and grafting.